2007
DOI: 10.1007/s11243-007-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and DNA binding studies of ruthenium(II) complexes: [Ru(bpy)2(dtmi)]2+ and [Ru(bpy)2(dtni)]2+

Abstract: Two new ruthenium(II) polypyridyl complexes ½Ru(bpy) 2 (dtmi)ðClO 4 Þ 2 (1) (dtmi = 3-(pyrazin-2-yl)-as-triazino [5,6-f]-5-methoxylisatin) and ½Ru(bpy) 2 (dtni)ðClO 4 Þ 2 (2) (dtni = 3-(pyrazin-2-yl)-as-triazino[5,6-f]-5-nitroisatin) have been synthesized and characterized by elemental analysis, FAB-MS, ES-MS and 1 H-n.m.r. The DNA-binding patterns of complexes were investigated by spectroscopic titration, viscosity measurements and thermal denaturation. The results indicate that the complexes (1) and (2) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Among the synthesized metal complexes copper complex acts as a higher metallointercalator compared to other complexes. Thus, the results specify that the binding order depends upon the ionic radius, size and charge on the metal ion, which indicate that the metal ion plays a crucial role in DNA binding affinity of these complexes …”
Section: Resultsmentioning
confidence: 74%
“…Among the synthesized metal complexes copper complex acts as a higher metallointercalator compared to other complexes. Thus, the results specify that the binding order depends upon the ionic radius, size and charge on the metal ion, which indicate that the metal ion plays a crucial role in DNA binding affinity of these complexes …”
Section: Resultsmentioning
confidence: 74%
“…Thus, due to constriction of phenyl at the intercalation site, binding ability of complex is reduced 27. On internal comparison, it is found that the electron‐withdrawing substituent on 4th position has high DNA binding affinity compared to that on 3rd position 28…”
Section: Resultsmentioning
confidence: 99%
“…The values of DG 0 T , DH 0 , and DS 0 for complexes 1, 2, and [Ru-(bpy) 2 (dtmi)] 2? [51] are shown in Table 3. The negative binding free energies suggest that the sum of the free energies of the free complex [Ru(bpy) 2 (ITAP)] 2?…”
Section: Thermal Denaturation Studymentioning
confidence: 99%